Toward Optimal Budget Utilization at the Department of Foreign Affairs: Focus on Foreign Service Posts and the International Commitment Funds (a zero-based budgeting attempt) - Federico M. Macaranas; Norma Lasala; Alain M. Maulion; Brenda B. Furagganan (Philippine Institute for Development Studies (PIDS), 2013)
This paper studies the optimization in the use of scarce budgetary resources available to the Philippine national government in fulfilling its role in the three pillars of foreign policy (traditional political-security areas, economic and social development concerns, and more recent engagement on the assistance to nationals). The lack of consistent data for longer-term analysis of benefits and costs in these three pillars and the inadequately defined value-addition of the Department of Foreign Affairs (DFA) in the One Country Team approach may have been brought in part by the misallocation of human resources; career officers must be trained further in knowledge management, benefit-cost and cost-effectiveness analysis, especially in the management of the International Commitments Funds for international organizations. Rationalization of procedures in the retention of financial proceeds from consular services, centralization of accounting and monitoring Foreign Service Posts funds, and write-offs of collections from other agencies for advances made by the DFA for administrative overhead are also suggested.
Keywords: 330; Philippines; economic diplomacy; knowledge management; foreign relations budget